Linguistic patterning of laughter in human-socialbot interactions - Perkins Booker, Nynaeve; Cohn, Michelle; Zellou, Georgia (Frontiers in Communication, 2024)
Laughter is a social behavior that conveys a variety of emotional states and is also intricately intertwined with linguistic communication. As people increasingly engage with voice-activated artificially intelligent (voice-AI) systems, an open question is how laughter patterns during spoken language interactions with technology. In Experiment 1, we collected a corpus of recorded short conversations (~10 minutes in length) between users (n=76) and Amazon Alexa socialbots (a voice-AI interface designed to mimic human conversational interactions) and analyzed the interactional and pragmatic contexts in which laughter occurred. Laughter was coded for placement in the interaction relative to various speech acts, as well as for phonetic patterning such as duration and voicing. Our analyses reveal that laughter is most commonly found when the content of Alexa’s speech is considered inappropriate for the discourse context. Laughter in the corpus was also largely short in length and unvoiced– characteristics which are commonly associated with negative social valence. In Experiment 2, we found that a separate group of listeners did not distinguish between positive and negative laughter from our dataset, though we find that laughs rated as more positive are also rated as more excited and authentic. Overall, we discuss our findings for models of human-computer interaction and applications for the use of laughter in socialbot conversations.